The Exiled Poet Maḥmūd Bayram Al-Tūnīsī - Ömer İshakoğlu (Şarkiyat Mecmuası)
Maḥmūd Bayram was born and raised in Egypt as a member of a Tunisian family. Although his circumstances prevented him from receiving a regular education, he eventually became a leading figure in society thanks to his intelligence and devotion to study. However, Bayram’s fighting spirit and sensitivity to injustice resulted in him being sentenced to exile by the colonial powers and the administrations under their control. Despite spending most of his life in exile under difficult conditions, he continued the literary pursuits that he had started in Egypt. He also worked as a manager and writer for various newspapers and magazines. Although he produced works in genres such as poetry, articles, stories, and maqāms, he was best known for his zadjal and song lyrics written in the local vernacular. Consequently, Bayram did not achieve the recognition he deserved in the literary world. This article, which addresses the absence of a private study of him in Turkish, examines the many literary genres in which Maḥmūd Bayram wrote and considers previously neglected personal aspects of his works. Alongside his literary identity, Bayram often adopted political and reformist structures and engaged with difficult struggles accordingly. While the title of folk artist was attributed to Bayram, this study demonstrates that he also produced works of high literary value. Thus, it would clearly seem beneficial to undertake individual studies or learned dissertations about his works in each literary genre.